1992
DOI: 10.1111/j.2044-8260.1992.tb00983.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐forms of the UK WAIS—R: Regression equations and their predictive validity in a general population sample

Abstract: A sample of 200 healthy subjects, representative of the adult UK population in terms of age, sex and social class distribution, were administered a full-length WAIS-R (UK). Regression equations were built to predict full-length IQ from a series of short-forms. The short-forms ranged from a two-subtest version proposed by Silverstein (1982) to a seven-subtest version proposed by Warrington, James & Maciejewski (1986). Regression equations, their standard errors of estimate and confidence intervals are presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 12 publications
0
36
0
Order By: Relevance
“…Neuropsychological evaluation included the Verbal Fluency Test, the Stroop Task (Stroop, 1935), an abridged version of Wechsler's Revised Intelligence Scale for Adults (Britton & Savage, 1966;Wechsler, 1989), including four subtests (Crawford et al, 1992), and the Wechsler Memory Scale (Wechsler, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…Neuropsychological evaluation included the Verbal Fluency Test, the Stroop Task (Stroop, 1935), an abridged version of Wechsler's Revised Intelligence Scale for Adults (Britton & Savage, 1966;Wechsler, 1989), including four subtests (Crawford et al, 1992), and the Wechsler Memory Scale (Wechsler, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…Intellectual ability was estimated using abbreviated age-appropriate Wechsler tests (Weschler, 1981(Weschler, , 1992) scored according to published equations (Crawford et al, 1992;Kaufman et al, 1996). Verbal IQ was employed for matching because it has been consistently reported that on average 22q11DS individuals have lower performance IQ than verbal IQ (Jacobson et al, 2010).…”
Section: Subjectsmentioning
confidence: 99%
“…All subjects completed the NART, STW (form A) and CCRT. The healthy control subjects also completed the short form of the Wechsler Adult Intelligence ScaleÐRevised (WAIS-R) as recommended by Crawford et al (1992), which consists of the subtests of comprehension, similarities, block design and object assembly.…”
Section: Control Groupmentioning
confidence: 99%
“…The purpose of the present study was to extend upon the ®ndings of Beardsall & Huppert (1997) by carrying out a further evaluation of NART, CCRT and STW in a sample of patients suering from dementia of the Alzheimer type (DAT). Furthermore, the validity of each of these three putative premorbid estimates was tested by comparing the correlations of each measure with current measures of intelligence derived using a short form (Crawford et al, 1992) of the Wechsler Adult Intelligence ScaleÐRevised (Wechsler, 1981) in a large sample of healthy control subjects.…”
mentioning
confidence: 99%